Sustainable Innovation in Community Service as an Effort to Build an Adaptive and Resilient Social Ecosystem - Susatyo Adhi Pramono; Endang Sri Wahyuningsih; Basuki; Irawan Dharma Sukowati; Muhammad Edwin Rachmanudin (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to enrich the body of knowledge related to community service, particularly in the context of sustainable innovation as an effort to develop an adaptive and resilient social ecosystem. The research employs a qualitative approach using a literature review method analyzed descriptively. Data were obtained from Google Scholar and various credible websites with a publication range from 1984 to 2026. Of the 50 articles identified in the initial stage, a rigorous selection process was conducted based on relevance, quality, and methodological suitability, resulting in 37 articles for further analysis. The findings indicate that sustainable innovation in community service plays a strategic role in enhancing individual and community capacities, strengthening social resilience, and fostering the development of adaptive social ecosystems. Innovative approaches that integrate technology, community participation, and multi-stakeholder collaboration have proven effective in improving program effectiveness and sustainability. Furthermore, the findings reveal that successful implementation is significantly influenced by policy support, access to resources, and the community’s ability to adapt to change. However, several challenges remain, including limited innovation literacy, lack of synergy among stakeholders, and financial constraints. Therefore, more integrated and sustainable strategies are required to optimize the role of innovation in community service.